The Road to Discovery Detector Alignment, Electron Identification, Particle Misidentification, WW Physics, and the Discovery of the Higgs Boson - Alison, John (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
The research presented here includes important contributions on the commissioning of the ATLAS experiment and the discovery of the Higgs boson. The thesis describes essential work on the alignment of the inner tracker during the commissioning of the experiment and development of the electron identification algorithm. The subsequent analysis focuses on the search for the Higgs boson in the WW channel, including the development of a method to model the critical W+jet background. In addition, the thesis provides excellent introductions, suitable for non-specialists, to Higgs physics, to the LHC, and to the ATLAS experiment.